ANALISIS KESALAHAN PENULISAN HURUF KAPITAL DAN PENGGUNAAN TANDA BACA PADA KARANGAN DESKRIPSI - Rezki Amelia Agustin; Dilla Fadhillah; Moh Iqbal Firdaus (Jurnal Dedikasi Pendidikan, 2023)
The problem in this study is that composing is often described as an activity that has not taken place as expected. Not a few students often experience difficulties in dealing with writing descriptions. Writing is expressing thoughts through writing. Errors in writing capital letters and using inappropriate punctuation often occur in student writing. Data collection activities in this study used observation techniques (observing) with note-taking techniques. The data collection method used in this research is documentation. Teacher and student interview data techniques. Test technique. Data analysis techniques use the Miles and Huberman concepts which include (1) data collection, (2) data reduction, (3) data presentation (4) conclusions. In this study, the data was in written form, in the form of errors in capital letters, punctuation and descriptive essays. Based on the results of the study, it was found that there were errors in the use of capital letters (A), full stop punctuation (.), (2) errors in the use of comma punctuation (,). In writing, one must understand the rules of writing, one of which is standard writing and the use of PUEBI, so that writing is in accordance with good and correct rules in writing capital letters, punctuation.